Legal Protection of Child Offenders in Restorative Justice–Based Criminal Investigations - Wahyono, Dodik; Bimantara, Gesa; Tina, Neli Agus (Jurnal Ilmu Hukum Kyadiren, 2026)
Legal protection for children as offenders constitutes a constitutional and statutory mandate that must be effectively realized through a restorative justice–based Juvenile Criminal Justice System. However, in investigative practice, the implementation of such protection continues to encounter various challenges. This study aims to examine the forms of legal protection afforded to child offenders during the investigation process at the Surabaya Police Headquarters, as regulated under the Juvenile Criminal Justice System Law and grounded in restorative justice principles, and to identify both normative and empirical obstacles in order to formulate strategies for optimizing legal protection. This research employs an empirical juridical method using statutory and sociological approaches, with data collected through interviews and document analysis. The findings reveal that legal protection and restorative justice mechanisms have been implemented, albeit not optimally, due to a limited number of specialized child investigators, weak inter-institutional coordination, and low levels of public legal awareness. The study concludes that optimizing legal protection for children requires strengthening institutional capacity, enhancing cross-sector coordination, and improving public legal literacy.